2008
DOI: 10.1121/1.2980441
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hearing loss and age on the benefit of spatial separation between multiple talkers in reverberant rooms

Abstract: This study investigated the interaction between hearing loss, reverberation, and age on the benefit of spatially separating multiple masking talkers from a target talker. Four listener groups were tested based on hearing status and age. On every trial listeners heard three different sentences spoken simultaneously by different female talkers. Listeners reported keywords from the target sentence, which was presented at a fixed and known location. Maskers were colocated with the target or presented from spatiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
178
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(210 citation statements)
references
References 44 publications
27
178
4
Order By: Relevance
“…This configuration was originally implemented to minimize the contribution of long-term head-shadow benefits to SRM (Noble et al 1997;Marrone et al 2008) but has since been adopted as a striking case in which the difference between NH and HI listeners is large. This paper describes related studies from three different laboratories that used the "symmetric masker" configuration to explore the interaction between target audibility and performance under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This configuration was originally implemented to minimize the contribution of long-term head-shadow benefits to SRM (Noble et al 1997;Marrone et al 2008) but has since been adopted as a striking case in which the difference between NH and HI listeners is large. This paper describes related studies from three different laboratories that used the "symmetric masker" configuration to explore the interaction between target audibility and performance under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although both NH and HL groups performed well above chance on the uncued task, the HL group performed more poorly than the NH group. This was expected on the basis of previous work showing that real or simulated hearing loss impairs one's ability to make use of differences in voice characteristics (Baer and Moore 1994;Mackersie et al 2001;Gaudrain et al 2007), masker fluctuations (Duquesnoy 1983;Festen and Plomp 1990;Bronkhorst and Plomp 1992;Lorenzi et al 2006), and spatial separation (Bronkhorst and Plomp 1989;Arbogast et al 2005;Marrone et al 2008) to understand a talker of interest. It also may be that reductions in spectrotemporal resolution would have reduced the salience of the target by, for example, blurring the distinction between forward and time-reversed speech.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we adopted the paradigm of Best et al (2007) to identify whether listeners with sensorineural hearing loss (HL) are able to use top-down attention to enhance speech intelligibility to the same extent as listeners with normal hearing (NH). Based on previous work, we expected HL listeners to be poorer overall at understanding speech in the presence of competition (e.g., Bronkhorst and Plomp 1992;Mackersie et al 2001;Arbogast et al 2005;Marrone et al 2008). This deficit is thought to arise from several factors including reduced audibility and reduced spectral resolution (Baer and Moore 1994;Gaudrain et al 2007;Moore 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has been observed that SRM is often inversely related to the severity of hearing loss (e.g. Marrone et al 2008). This raises the question of whether in some cases apparent spatial deficits might be related to reduced audibility in spatialized mixtures.…”
Section: Introductionmentioning
confidence: 99%